مفهوم "الأعراب" في القرآن الكريم دارسة مصطلحية - بن أودينة, يوسف (University of Eloued جامعة الوادي, 2024)
عتبر المصطلح القرآني من أهم المصطلحات التي تلقى الاجماع في وضعه؛ لأنه ذكر في كتاب الله العزيز الحكيم؛ وإن اختلف في مفهومه من قبل المفسرين، ولأن المصطلح القرآني لا يتبدل ولا تتغير دلالاته بل تتسع لتعم كل المستجدات في مجاله؛ ومن أجل هذا كان حريا بنا أن نجعله هو الفيصل بين الواضعين للمصطلحات. ومن بين المصطلحات التي أثارت خلافا بين العلماء وخاصة في العصر الحديث مصطلح "الأعراب" الذي ذكر في القرآن الكريم في عدة مواضع وفي سياقات تظهر من خلال القراءة الأولى أنها مختلفة وربما متضاربة. وسنحاول من خلال هذه المداخلة أن نستجلي معنى كلمة "الأعراب" في اللغة ومن خلال كتب المفسرين من أهل السنة والجماعة ومن طائفة الشيعة، من المتقدمين والمتأخرين؛ وسنجمع أقوالهم لمعرفة أقوالهم حول هذا المصطلح وتوجيههم للآيات التى ذكر فيها لفظ "الأعراب" ، ومن خلال ذلك كله يمكننا أن نهتدي لقول فصل في هذه المسألة التي تثار من حين لآخر خاصة في زمننا هذا الذي كثر فيه الادعاء بين الطوائف والعرقيات. Abstract: The Quoranic term is one of the most important terms that were met with unanimity when they were developed because it is mentioned in the Book of Allâh, the All-Mighty, the All-Knowing. Despite the difference of opinion among the exegetes concerning its concept, the connotation of the Quranic term does not only remain unchanged, but it is extended to encompass all the updates in its field, and for this, we should have made the the judge between terminologist. The term "a‘rāb" (Arab Bedouins) is one of the terms that has sparked disagreement among scholars, especially in modern times. It was mentioned in the Holy Quran in several places and in contexts that appear from the first reading that they are different and possibly conflicting. In this presentation, we will try to search for the meaning of the word "a‘rāb" in the language and in the books of past and present exegetes from Ahl as-Sunnah wa’l Jama’ah (People of the prophetic tradition and the community) and the Shia Community, then we will collect their sayings to know what they have said about this term and their interpretations of the verses in which the word "a‘rāb" is mentioned. Through all these, we can be guided towards the final say in this matter which is raised from time to time, especially in our time that is abundant with inter-ethnic allegations
Keywords: المصطلح، الأعرب، البادية، أعجمي، عربي